2014
DOI: 10.1073/pnas.1402773111
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and gamma oscillations characterize feedback and feedforward processing in monkey visual cortex

Abstract: This Feature Article is part of a series identified by the Editorial Board as reporting findings of exceptional significance.Edited by Terrence J. Sejnowski, Salk Institute for Biological Studies, La Jolla, CA, and approved August 8, 2014 (received for review February 22, 2014) Cognitive functions rely on the coordinated activity of neurons in many brain regions, but the interactions between cortical areas are not yet well understood. Here we investigated whether lowfrequency (α) and high-frequency (γ) osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

148
832
10
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 873 publications
(991 citation statements)
references
References 96 publications
148
832
10
1
Order By: Relevance
“…Intracranial electrophysiological recordings in animals have linked neuronal oscillations in different frequency bands to the cortical feedforward and feedback information flow and to cortico-subcortical interactions (2)(3)(4)(5). In line with these findings, electrophysiological recordings in animals have also demonstrated that changes in α-, β-, and γ-bands can be localized to specific cortical layers (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 72%
“…Intracranial electrophysiological recordings in animals have linked neuronal oscillations in different frequency bands to the cortical feedforward and feedback information flow and to cortico-subcortical interactions (2)(3)(4)(5). In line with these findings, electrophysiological recordings in animals have also demonstrated that changes in α-, β-, and γ-bands can be localized to specific cortical layers (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 72%
“…From this perspective, the phase locking of scalp EEG data as accounted for by microstates and related models may probably better be considered as signatures of transient large-scale processes that organize neuronal excitability rather than the signatures of neuronal communication within these cycles of excitability itself. One may further argue that these latter processes that implement communication itself may take place on spatial scales that are mostly below the resolution of scalp EEG data and typically need to be resolved by recording local field potentials (van Kerkoerle et al, 2014). The fact that combined EEG-fMRI data has shown that the topographic appearance of specific transient states of EEG synchronization (that are assumingly cortical) covaried with the spatial distribution of thalamic activity (Schwab et al, 2015) may further support this view, since the thalamus is a well-known pace-maker for cortical cycles of M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…interactions to assess brain connectivity (Pascual-Marqui et al, 2011), and there is good electrophysiological evidence that these lags exist and play a functional role (van Kerkoerle et al, 2014). However, the microstate model contains a strong and a priori constraint on simultaneity, which excludes the existence of significant lags within a microstate.…”
Section: Many Eeg Studies Have Employed Frequency Domain Measures Ofmentioning
confidence: 99%
“…More specifically, high frequency oscillations occur predominantly in granular layers 3 and 4, while alpha (8-12 Hz)/beta (13-30 Hz) oscillations occur predominantly in infra-granular layers 5 and 6 (Bastos et al, 2015;van Kerkoerle et al, 2014). In addition to stimulus parameters, the amplitude and frequency of high-frequency oscillations in visual cortices can also be influenced by central states, such as attention.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha generators have been found in different layers of both striate and extra-striate visual areas (Bollimunta et al, 2008(Bollimunta et al, , 2011Mo et al, 2011;Haegens et al, 2015;van Kerkoerle et al, 2014), and are known to be modulated in activity by both cortico-cortical and recurrent thalamo-cortical (TC) communication (Steriade et al, 1990), influenced by thalamic nuclei such as the lateral geniculate nucleus (LGN), the pulvinar nucleus, and the thalamic reticular nucleus (TRN). Evidence is growing that these different thalamic nuclei play different roles in sensory information processing, both spatially (i.e., across the visual hierarchy) and temporally (i.e., during early feedforward and later feedback processing), raising the possibility that aberrant alpha-band activity in visual cortices may in part reflect aberrant TC-interactions.…”
mentioning
confidence: 99%